(untitled) (Emancipação, 2021)
This article analyzes aspects related to rural succession, which occur in family farming establishments. The information was collected, using the case study methodology, through 219 interviews, composed of closed questionnaires. They were carried out in the municipalities of Francisco Beltrão, Itapejara D’Oeste and Verê, in the state of Paraná (PR); Concórdia, in Santa Catarina (SC); Augusto Corrêa, Tomé-Açú and Viseu, in Pará (PA); Petrolina, in Pernambuco (PE); and in the municipalities of Uauá and Cruz das Almas, in Bahia (BA), a total of ten municipalities, in the five Brazilian states. This investigation aims to seek evidence on the social, economic and cultural relations that govern and influence the generational succession in rural establishments. The study made it possible to prove that almost half of family farmers have no guarantee of possible successors, as a significant part of them want other forms of monetary income, outside the establishments, including through emigration.